Integrated metabolome and transcriptome analysis identifies candidate genes involved in triterpenoid saponin biosynthesis in leaves of Centella asiatica (L.) Urban - Wan, Lingyun; Huang, Qiulan; Li, Cui; Yu, Haixia; Tan, Guiyu; Wei, Shugen; El-Sappah, Ahmed H.; Sooranna, Suren; Zhang, Kun; Pan, Limei; Zhang, Zhanjiang; Lei, Ming (Frontiers in Plant Science, 2024)
Centella asiatica (L.) Urban is a well-known medicinal plant which has multiple pharmacological properties. Notably, the leaves of C. asiatica contain large amounts of triterpenoid saponins. However, there have only been a few studies systematically elucidating the metabolic dynamics and transcriptional differences regarding triterpenoid saponin biosynthesis during the leaf development stages of C. asiatica. Here, we performed a comprehensive analysis of the metabolome and transcriptome to reveal the dynamic patterns of triterpenoid saponin accumulation and identified the key candidate genes associated with their biosynthesis in C. asiatica leaves. In this study, we found that the key precursors in the synthesis of terpenoids, including DMAPP, IPP and β-amyrin, as well as 22 triterpenes and eight triterpenoid saponins were considered as differentially accumulated metabolites. The concentrations of DMAPP, IPP and β-amyrin showed significant increases during the entire stage of leaf development. The levels of 12 triterpenes decreased only during the later stages of leaf development, but five triterpenoid saponins rapidly accumulated at the early stages, and later decreased to a constant level. Furthermore, 48 genes involved in the MVA, MEP and 2, 3-oxidosqualene biosynthetic pathways were selected following gene annotation. Then, 17 CYP450s and 26 UGTs, which are respectively responsible for backbone modifications, were used for phylogenetic-tree construction and time-specific expression analysis. From these data, by integrating metabolomics and transcriptomics analyses, we identified CaHDR1 and CaIDI2 as the candidate genes associated with DMAPP and IPP synthesis, respectively, and CaβAS1 as the one regulating β-amyrin synthesis. Two genes from the CYP716 family were confirmed as CaCYP716A83 and CaCYP716C11. We also selected two UGT73 families as candidate genes, associated with glycosylation of the terpenoid backbone at C-3 in C. asiatica. These findings will pave the way for further research on the molecular mechanisms associated with triterpenoid saponin biosynthesis in C. asiatica.